Nanostructure and magnetic anomaly of mechanosynthesized Ce1-xYxO2-δ (x ≤ 0.3) solid solutions. (January 2021) - Fabián, Martin; Menzel, Dirk; Yermakov, Anatoly Ye; Kolev, Hristo; Kaňuchová, Mária; Shi, Jianmin; Kováč, Jaroslav; Kostova, Nina; Da Silva, Klebson L.; Senna, Mamoru; Harničárová, Marta; Valíček, Jan; et al.
Abstract: Electromagnetic properties of complex oxide solid solutions containing Ce and Y attract increasing interests due to their high application potential. Their properties are known to be dependent on many factors including grain size and crystal defects. Here we focus on unique features of nanocrystalline Ce1-x Yx O2-δ (x ≤ 0.3) solid solutions prepared via a mechanosynthesis. Mechanically activated CeO2-δ and mechanosynthesized Ce1-x Yx O2-δ exhibit room-temperature ferromagnetism. The saturation magnetization reaches maximum for the Ce0.9 Y0.1 O2-δ solid solution. XPS and Raman spectra show that Ce 4+ ions are partially reduced to Ce 3+, with simultaneous introduction of oxygen vacancies accumulated on surface of the solid solutions. An analysis of the experimental magnetization data and the determination of both the spin state and the concentration of magnetic carriers revealed that a small part of the Ce 3+ spins (<1%) is responsible for the magnetic state of the Ce1-x Yx O2-δ system. Existence of clusters with a short-range antiferromagnetic order is also suspected. Graphical abstract: Image 1 Highlights: Mechanosynthesized Ce1-x Yx O2-δ solid solutions exhibit room temperature ferromagnetism. Experimental magnetization curves are described by the Brillouin function. Free Ce 3+ magnetic carriers possess low concentration. Antiferromagnetic short-range interaction between Ce 3+ carriers is also observed.